The clinical significance of allergen-specific IgG4 in allergic diseases - Qin, Lu; Tang, Lan-Fang; Cheng, Lei; Wang, Hui-Ying (Frontiers in Immunology, 2022)
IgG4 is a particular subclass of IgG antibody with the unique molecular feature of Fab-arm exchange and consequent biology of bi-specificity of antigen binding and mono-valent behavior. With the low affinity to C1q and FcγReceptor, IgG4 exhibits a non-inflammatory feature for its incapability to form immune complexes and activate the complement pathway. Moreover, IgG4 is produced similarly to IgE production and is considered a modified immune response to switch IgE response under certain status. It also could counteract IgE-activated inflammation. However, the clinical significance of IgG4 in allergic diseases is complex and controversial. Three viewpoints have been suggested to describe the role of IgG4. IgG4 acts as a tolerance–inducer. It plays a protective role under repeated and rapid incremental dosing of allergen exposure in allergen immunotherapy (AIT), with supplemented data of cat allergy in raisers and venom desensitization in beekeepers. Another viewpoint accepted by the mainstream specialists and guidelines of Food Allergy and Management of different countries points out that food-specific IgG4 is a bystander in food allergy and should not be used as a diagnostic tool in clinical work. However, eosinophilic esophagitis (EoE) investigation revealed a direct clinical relevance between physiopathology and serum IgG4 in cow milk and wheat. All those indicate that allergen-specific IgG4 plays a multifacial role in allergic diseases, protective or pathogenic, depending on different allergens or exposure conditions.